If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 37 = 7x + 47 Reorder the terms: 37 + 5x = 7x + 47 Reorder the terms: 37 + 5x = 47 + 7x Solving 37 + 5x = 47 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 37 + 5x + -7x = 47 + 7x + -7x Combine like terms: 5x + -7x = -2x 37 + -2x = 47 + 7x + -7x Combine like terms: 7x + -7x = 0 37 + -2x = 47 + 0 37 + -2x = 47 Add '-37' to each side of the equation. 37 + -37 + -2x = 47 + -37 Combine like terms: 37 + -37 = 0 0 + -2x = 47 + -37 -2x = 47 + -37 Combine like terms: 47 + -37 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| x^3-3x^2+2x=60 | | 45=4x+15 | | 7a^2x^2+4ax-8=0 | | 17x-4=180 | | .8(g+15)=24 | | 23=1-4x+6 | | 9x+42x+49=0 | | in(n^2+12)=ln(-9n-2) | | x^2-7x+10=180 | | 9a^2+4a+40=0 | | (t+4)5=15 | | 3+(4x)=48 | | 21+x=-1 | | (x+5)(x+2)=x^2+7x+10 | | 1.55=.08x-0.45 | | 4r^3-10r^2-14r=0 | | 2n-3=-6+n | | 3X*X=675 | | 109-5x=-95+12x | | x+9=64 | | 2n-3=6+n | | 7a^2-13a+6=0 | | (x+1)(x+3)(x+5)=48 | | 7x-5y=12fory | | 3n-3=-6+n | | x+25=135 | | 11-2x=3(3x-2)-5 | | -6.4(r-4)=-5.9r+28.45 | | cos^2x-3cosx-4=0 | | 26m=182 | | 7x+7=8x-3 | | 4z^2+8=0 |